Rancang Bangun Sistem Informasi Pemantauan Perkembangan Mitra Binaan pada Pelindo III Cabang Benoa Bali - Erwin Pramastya Sabatini; Arifin Puji Widodo; Tutut Wurijanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
The problem in PKBL activity of benoa port is based on PKBL's loan report in 2011, there is 100% total bad debt with the details 15 bad debt of 15 loans. and from the PKBL's loan report in first semester 2012, there is 87% total bad debt with the details 26 bad debt of 30 loans. the percentages amount of bad debt is caused by mitra could not adequate to pay their loan. PKBL's officer difficult to monitor when partner could not settle their loan. In order to solve the problem, they need monitoring information system of fostered partner which give benefit to monitor financial condition of fostered partner. system will monitor with liquidity factor, solvency and profitability With the monitoring information system of fostered partner, PKBL's officer obtain the information about partner's result of paying ability asessment, information about partner's result of financial eficiency assessment and information about partner's result of determination founding assessment.